Perception of tennis ball flight in an immersive three-dimensional visual display - Ida, H.; Fukuhara, K.; Takahashi, M.; Ishii, M.; Inoue, T. (Japanese Journal of Sport Psychology, 2010)
The Cave Automatic Virtual Environment (CAVE), which is a computer-simulated 3D virtual reality (VR) system, is expected to provide sport learners with interactive and immersive learning materials. The purpose of this study was to reveal perceptual characteristics of tennis players when they viewed the tennis ball flight reconstructed in CAVE. The visual stimuli of this study were reconstructed based on the actual measured values of the tennis court and the ball flight. Perceptual performances, subjective impression scoring and shot type discrimination (flat, topspin and slice), were assessed by varying the conditions of three visual VR settings: binocular disparity, screen number, and viewpoint. The augmented-disparity setting was likely to induce a higher sense of discomfort than the no-disparity and normal-disparity settings. The four-screen condition was more likely to induce a correct response than the one-screen condition. The viewpoint of the umpire induced a significantly higher sense of discomfort than the field player viewpoints, and the viewpoint close to the approaching ball made it more difficult to discriminate the shot type. This research was a pilot study on sport perception in VR, and the results will contribute to the construction of sport-simulating VR systems.